Readiness for online learning among foreign language undergraduates in a private university in Malaysia / Mohd Hafizul Ismail, Basyirah Che Mat and Siti Nur Dina Mohd Ali - Ismail, Mohd Hafizul; Che Mat, Basyirah; Mohd Ali, Siti Nur Dina (Universiti Teknologi MARA, 2022)
Increasing numbers of COVID-19 cases in Malaysia forced the authority to enforce the Movement Control Order since March 2020. This order requires students in Malaysia to remain at home while learning via distance and online learning modes. This study aimed to assess the readiness of Foreign Language (FL) students in Malaysian private universityy in transition from face-to-face learning to online learning. This study employed quantitative research whereby the data was collected from 120 FL students using an online questionnaire. Computer/internet self-efficacy, self-directed learning, learner control, motivation of learning, and online communication self-efficacy are the five variables used to assess online learning readiness (OLR). The findings showed that most FL students are ready to learn online during the pandemic. Results show that the computer/internet self-efficacy the most significant OLR variable. According to the results, students were confident in obtaining any information on the internet and using the online learning platform in their studies. In the midst of the COVID-19 pandemic, the research adds to fundamental understanding of students' perceptions on shifting from face-to-face learning to online learning, as well as examining online learning readiness in language learning setting.